Implementasi Pendidikan Antikorupsi untuk Anak Usia Dini - Yayuk Rahayu (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2019)
This research aims to implemented anti-corruption education in early childhood. Education of the past is an important phase to internalize the values of anticorruption in children in their lives, especially the honest character. The importance of soaring important values in the first century due to early primary education from the determination of the child's character determinants in the future Knowledge and attachments that Receive children in the early days of their lives will be kept and shown to the children and will affect the personality to adulthood. Anticorruption values include honest, independent, responsible, simple, courageous, just as the basis for the establishment of corruption-free freedom. Implementation of anti-corruption education can use the media following the planting of character values. Embedding honesty through traditional methods, such as lectures or patronizing, without exemplifying will not form a character in a long time. Anticorruption education is very important to be applied early.